Strengthening Religious Moderation and Social Integration in Padak Guar Village, Sambelia District: A Case Study for Promoting Sustainable Peace in Pluralistic Communities - Sejati, Kharisma Rindang; Wahyudi, Very; Nulhakim, Lukman (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
This study explores the implementation of religious moderation in Padak Guar Village, Sambelia District, serving as a case study to illustrate the integration and tolerance among religious communities. Drawing on qualitative data obtained through interviews with various religious leaders, the research reveals that the community embraces the principles of wasathiyah (religious moderation), emphasizing balance, justice, and inclusivity in social interactions. The findings indicate that these principles have contributed to fostering social harmony within a pluralistic environment. This article further examines the supporting factors that enable the practice of religious moderation in Padak Guar, the challenges encountered by the community, and proposes strategic recommendations to sustain peaceful coexistence amid religious diversity.